The Pengaruh Media TikTok dan Faktor Pertemanan terhadap Pengambilan Keputusan dalam Belanja Online di TikTok Shop: (Studi Mahasiswa Asrama Sukamara di Kota Palangkaraya) - Irfani Irfani; Luluk Tri Harinie; Meylinda Sukmani; Meitiana Meitiana (SENTRI: Jurnal Riset Ilmiah, 2026)
This study looks at how TikTok media and peer influence affect online buying decisions among students at the Sukamara Dormitory in Palangkaraya City. The rapid growth of digital technology and social commerce has changed social media platforms. TikTok has shifted from being purely for entertainment to offering integrated online shopping with features like short videos, live streaming, and TikTok Shop. For university students, TikTok has become a main source of product information and purchase prompts. Peer relationships play a key role in shaping buying behavior through recommendations, discussions, and social validation. This research is important because students in dormitories have many social interactions that can strengthen both digital and social influences on their purchasing choices.This study uses an explanatory research design with a quantitative approach. Data were collected through structured questionnaires given to all 96 students at Sukamara Dormitory using a census method. The analysis involved descriptive statistics, multiple linear regression analysis, and hypothesis testing with SPSS software to explore the effects of the independent variables.Based on the results of the R² test (value 0.350 = 35.0%) and the results of the study indicate that TikTok media has a significant positive influence on online purchasing decisions, and peer influence also significantly influences students' purchasing choices. In addition, TikTok media and peer influence together have a significant impact on online purchasing decisions. These findings emphasize the need to combine digital media strategies with social influence factors. This study concludes that understanding how social media platforms interact with peer dynamics is crucial for creating effective digital marketing strategies and promoting responsible online shopping habits among students.